Volatile sulphur compounds in morning breath of human volunteers - Snel, Johannes; Burgering, Maurits; Smit, Bart; Noordman, Wouter; Tangerman, Albert; Winkel, Edwin G.; Kleerebezem, Michiel (Archives of oral biology, 2011)
Morning breath contains elevated concentrations of volatile sulphur components (VSCs). Therefore, morning breath is recognised as a surrogate target for interventions on breath quality. Nevertheless, factors influencing morning breath are poorly understood. Our aim was to evaluate concentrations of VSC at the time of awakening. A procedure was developed to collect breath samples at home. Intra- and inter-person variations were determined in two small studies based on measurements of hydrogen sulphide, methyl mercaptan and dimethyl sulphide in healthy volunteers. Highest levels of VSC were found directly after waking up, followed by a significant decline afterward. Considerable day-to-day variation was found, but could not be linked to dietary intake. A significantly higher concentration of H 2S and CH 3SH was observed in the group of female subjects compared to males. When morning breath is used as a target for interventions, breath collected at the time of or shortly after waking up is preferred over breath collected later during the morning. Gender plays an important role in VSC levels, and should be taken into account.